The Role of The Police in Investigations of Corruption Criminal Acts Involving Notaries - Kurniawati, Umi Hani (TABELLIUS: Journal of Law, 2025)
Abstract. The research entitled "The Role of the Police in Investigating Corruption Crimes Involving Notaries" examines the Authority and Role of the Police in Conducting Investigations of Corruption Crimes Involving Notaries, as well as to explore the extent of the Police's efforts in Balancing the Interests of Law Enforcement and Protection of the Notary Profession in Investigations of Corruption Crimes, which is expected to provide deeper insight into the dynamics of investigations and the need for effective law enforcement. This research method uses a normative legal approach, meaning that the research is conducted using a literature study approach and a statute approach. Data type The type of data uses secondary data obtained from a literature study. The analysis in this study is prescriptive. The results of the study show that although the police have an important role in investigating corruption crimes involving notaries, they face various challenges, such as the confidentiality of the notary profession and the complexity of the case. This study recommends improving training for investigators, strengthening inter-agency cooperation, and changing policies that support law enforcement. With these steps, it is hoped that the police can be more effective in eradicating corruption and maintaining the integrity of the notary profession.Keywords: Corruption Crime; Investigation; Notary; Police.